TEKNOLOGI DAN MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - soheh, Moh.; Subhan, Moh (Universitas Islam Madura, 2017)
Educational technology is defined as a design of learning that is designed by using certain methods and presented with various learning tools intended to facilitate learning. Learning media are all sesuau that can channel messages that can stimulate the mind, persaaan, attention, and willingness of students so as to encourage the happening of the process bejar to students. Learning technology began to emerge in line with the development of education that gave birth to the educational revolution. The educational revolution took place at four stages of the revolution. The first revolution occurs when parents are unable to provide education to their children so they have to entrust to a teacher, both because teachers have the desire to provide education to many students at once so that the occurrence of classical learning, the third occurs when teachers have the desire to provide education to many students at the same time in a shorter time because learners are equipped with learning materials. This revolution occurs when the development of advanced technology began rapidly, then the teacher wanted to use it for the purposes of education with the aim that learning bias done quickly and efficiently with students equipped with the expertise to use various technologies to prepare independent students.